THE IMPACT OF NATURAL RESOURCES USE AND CONSUMPTION ON INTERNATIONAL TRADE - ZVARYCH, Roman; LINHAI, Wei (Journal of European Economy, 2024)
The article analyzes the utilization of various resources, the speed of their consumption and the impact on the environment. The economic dynamics surrounding natural resources in international trade are subject to comprehensive examination. This analysis encompasses the utilization patterns of energy, minerals, agricultural commodities, water, and biological resources within the framework of their influence on international relations. The methodology for analyzing information on global tendencies in natural resources trade is applied to substantiate recommendations aimed at their balanced utilization in the macroeconomic policy of sustainable development. On the basis of the analysis of the status and role of natural resources in international trade, recommendations for states regarding the formulation of sustainable development and natural resource management policies are provided. JEL: F13, Q27, Q37, P28.